All‐Sprayable Hierarchically Nanostructured Conducting Polymer Hydrogel for Massively Manufactured Flexible All‐Solid‐State Supercapacitor. Issue 6 (24th April 2019) - Han, Yu; Chu, Xiang; Zhang, Haitao; Huang, Haichao; Tian, Guo; Wang, Zixing; Gu, Bingni; Chen, Ningjun; Deng, Wen; Deng, Weili; Yang, Weiqing
Abstract : The low‐cost processing and uniquely structured design of conducting polymer hydrogels (CPHs), with the advantages of both conducting polymers and 3D frameworks, are the keys to their wide commercial application in next‐generation flexible solid supercapacitors. Herein, an all‐sprayable hierarchically nanostructured polyaniline–phytic acid conducting polymer hydrogel (pp‐CPHs) for upgradable art patterns and massively manufactured supercapacitor electrodes is presented. Ascribing to fully anticipating the efficient electrode–electrolyte interface of 3D porous nanostructures constructed by interconnected nanorods, the pp‐CPH‐based flexible all‐solid‐state supercapacitors exhibit an excellent areal capacitance of 91 mF cm −2 at a current density of 1 mA cm −2 and a drastically improved cycling stability with 93.5% capacitance retention after 10 000 cycles at 5 mA cm −2 . In addition, the electrochemical performance of this device can be constantly maintained under various mechanical loadings such as bending and twisting. Also, this device shows a remarkable integration ability from its universal tandem and parallel connections. Unambiguously, these aforementioned merits of pp‐CPH‐based flexible all‐solid‐state supercapacitors make it an ideal maneuver for the massive fabrication of flexible power supply. Abstract : Polyaniline–phytic acid conductive polymer hydrogels with 3D hierarchical interconnected coral‐like structures are successfully designed. This hydrogel can be massively sprayed for the fabrication of high‐performance flexible solid‐state supercapacitors. As a result, such a supercapacitor achieves a highly areal capacitance (91 mF cm −2 at 1 mA cm −2 ) and an excellent cycling stability (93.5% capacitance retention over 10 000 charge–discharge cycles).